Evidence for a curvilinear relationship between burnout and years of coaching experience - Bradford, S. H.; Pugh, S. F.; Heitman, R. J.; Kovaleski, J. E.; Keshock, C. M. (The Sport Journal, 2012)
The purpose of this study was to determine if the relationship between burnout, as measured by the Maslach Burnout Inventory (MBI), and years of coaching experience was curvilinear for male high school coaches. Hierarchical regression found a significant quadratic component for the MBI subscales of Emotional Exhaustion (p<.05) and Depersonalization (p<.05). No significant linear or quadratic relationships were found for the Personal Accomplishment subscale. These results suggest that two categories of burnout as measured by the MBI (Emotional Exhaustion and Depersonalization) do not increase in a linear fashion with coaching experience rather a curvilinear shape was found. Male high school coaches with fewer years of experience suffered more emotional exhaustion and depersonalization than those with more years of experience.